Kajian Strategi Pembelajaran Jarak Jauh Yang Menunjang Kesehatan Mental Di Sekolah Dasar - Evita Adnan; Maratun Nafiah (Jurnal Sains Sosio Humaniora, 2021)
The purpose of this research is to describe the elementary school teacher’s strategies in applying remote learning during pandemic Covid – 19 in Kabupaten Bogor, especially in Klapanunggal region, in order to maintain student’s mental health. From surveys, interviews, and FGD conducted, this research find that most of the teachers basically have adequate knowledge about the mental health issues and some already consider the issues on the process designing and implementing the strategies. Nevertheless, those strategies can’t completely implemented since there are some technical obstacles and the situation of pandemics, include the remote learning policy itself, affect the mental health for both teachers and students. Remote learning reduce the spiritual aspect in learning or called “mattering” such as simple chit – chat and greetings before and during class activities so that leads to student’s demotivation on learning.